2019
DOI: 10.3390/ani9070439
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Canine Babesia Species Prevalent in Pet Dogs of Punjab, Pakistan

Abstract: Canine babesiosis is a serious threat to dogs’ health worldwide, caused by the intra-erythrocytic Babesia species. The present study was carried out in pet dogs presented at three clinics of Lahore and one of Narowal in Punjab, Pakistan. Two hundred blood samples (50 from each clinic) were collected and screened by microscopy for Babesia spp. Out of 200 samples, 84 (42%) were found to be positive for babesiosis. The highest number of positive cases (50%) was recorded in dogs at Narowal clinic. Non-significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
1
2
0
2
Order By: Relevance
“…The highest incidence of canine babesiosis was observed in April and June, which is similar to the results of Tayyub et al [33]. Furthermore, the highest number of positive cases occurred in spring and summer, likely because of increased exposure to ticks during these seasons [1] and warm and humid climate conditions favoring disease transmission by vectors [33].…”
Section: Discussionsupporting
confidence: 80%
“…The highest incidence of canine babesiosis was observed in April and June, which is similar to the results of Tayyub et al [33]. Furthermore, the highest number of positive cases occurred in spring and summer, likely because of increased exposure to ticks during these seasons [1] and warm and humid climate conditions favoring disease transmission by vectors [33].…”
Section: Discussionsupporting
confidence: 80%
“…Babesiosis can be diagnosed by microscopic detection technique including thin, thick, brain and hemolymph smear, serological technique including indirect flouroscent antibody test (IFAT), Competitive Enzyme linked immunosorbent assay (cELISA), Immunochromatography (ICT), complement fixation test (CFT), and molecular techniques including DNA probes, Polymerase Chain Reaction (PCR), nested PCR, Real-time PCR, Restriction fragment length polymorphism (RFLP) PCR, Reverse line blot hybridization (RLB), loop-mediated isothermal amplification (LAMP) The most common methods used for the diagnosis is thin blood smear technique and microscopic examination of the stage of Babesia parasite in the erythrocytes or blood and tissue fluid. Chronic stages of these diseases are challenging for the examination under microscope of invasively acquired specimen and treatment for these cases [ 32 , 33 ].…”
Section: Diagnosismentioning
confidence: 99%
“…However, a study from North America identified 18 cases of B. canis infection among 9367 blood and tissue samples from presumably symptomatic dogs, despite this part of the world being non-endemic for D. reticulatus ticks [5]. Similarly, B. canis infections in dogs have been recognized in other places where D. reticulatus ticks do not occur, including Finland, southern Italy (Campania region), northwestern Iran, the Punjab province in Pakistan, and the Henan province in China [52,173,176,177,182]. Moreover, high seroprevalence has been observed in kenneled dogs with unknown health status in southern Italy (Strait of Messina), which is also a nonendemic region for the parasite's vector [171].…”
Section: Prevalence Of Babesia Canismentioning
confidence: 99%